FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN ASEPTOR METODE KONTRASEPSI JANGKA PANJANG (MKJP) DI WILAYAH KERJA PUSKESMAS TANJUNG RAJA KABUPATEN OGAN ILIR - Jeni Malista; Siti Aisyah Hamid; Syarifah Ismed; Meriska Riski (LPPM STIKes Mitra Adiguna, 2023)
Family Planning (KB) is an action that helps married couples to avoid unwanted pregnancies, get the desired birth, regulate the interval between pregnancies, control the time of birth in a relationship with husband and wife and determine the number of children in the family. Population increase is a big problem in developing countries in the world, one of which is Indonesia which is a developing country with the largest population after China, India and the United States. The MKJP method is expected to regulate the rate of population growth. This type of research is quantitative using analytical survey methods, namely surveys or research that finds how and why health phenomena occur with a